ANALISIS DAMPAK LALU - LINTAS (ANDALALIN) PADA JALAN T.UMAR DITINJAU DARI TATA RUANG KOTA BANDA ACEH - Ayuza Jria Puspita; Mirza Irwansyah; Noer Fadhly (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Syiah Kuala, 2012)
Abstract: Government regulation of Banda Aceh city the Urban Spatial Planning year 2009-2029 in which the site T.Umar road is earmarked for trade and services regional. T.Umar road area is the center of the Banda Aceh urban which have the heavy traffic condition especially in the morning and late afternoon, this is due to the limited road capacity, limitations of the road network, intersection arrangements, and limited parking provision. Divided into four zones of the study area and 10 points (A - I). On recapitulation and the calculations of the rise and the biggest drag on the business day is CD 1692 Smp/hour point and F-G 2511 smp/h, on a Sunday There is also C-D 2901 smp / hour point. While the largest traffic percentage result is 23% on F-G point and I-J point, and Sunday C-D 30% point. On working day, F-G roads a critical degree of saturation at 1,16 Monday morning, it is because of the activities in the morning. Meanwhile, on Monday afternoon at C point to E point the degree of saturationhas already saturated, that is characterized by the value of DS of 1,09. Troubled zones in C-E point is an area that has a function instead of the trade and services as outlined in the city of Banda Aceh RTRW 2009-2029. The troubled zone due to the occurrence of a mixed land use (mixed use). this is what makes the imbalance development region so that the land use. In this case Spatial planning should follow what is already regulated by Government that do not alter the function of which is included in the Spatial Plan of the City. Active role of the public who pass through T.Umar road is necessary not only to limit and regulate space and community activities, but also provide encouragement and opportunities to community and participate in spatial activities by observing regulations.Keywords : Rise and drag, Spatial, the Spatial City.Abstrak: Peraturan pemerintah Kota Banda Aceh pada Rencana Tata Ruang Kota Banda Aceh Tahun 2009-2029 dimana lokasi Jalan T.Umar ini diperuntukkan untuk kawasan perdagangan dan jasa. Kawasan Jalan T.Umar merupakan pusat Kota Banda Aceh yang memiliki kondisi lalu - lintas yang padat terutama pada pagi sore hari, hal ini disebabkan oleh kapasitas jalan yang terbatas, keterbatasan jaringan jalan, pengaturan persimpangan, serta keterbatasan penyediaan parkir. Daerah penelitian dibagi 4 zona dan 10 titik (A-I). Pada perhitungan rekapitulasi bangkitan dan tarikan terbesar pada hari kerja adalah titik C-D 1.692 smp/jam dan F-G 2.511 smp/jam, pada hari Minggu juga terdapat pada titik C-D 2.901 smp/jam. Sedangkan hasil persentase lalu lintas terbesar 23 % pada titik F-G dan titk I-J, pada hari Minggu titik C-D 30%. Pada hari kerja ruas jalan F-G derajat kejenuhan kritis pada Senin pagi hari 1,16, hal ini di karenakan aktifitas di pagi hari. Sedangkan pada Senin sore pada titik C ke titik E derajat kejenuhan sudah jenuh ditandai dengan nilai D/S sebesar 1,09. Zona yang bermasalah pada titik C-E merupakan kawasan yang memiliki fungsi bukan kawasan perdagangan dan jasa seperti yang tertera pada RTRW Kota Banda Aceh 2009-2029. Zona yang bermasalah diakibatkan terjadinya penggunaan lahan yang bercampur (mixed use). Hai ini yang membuat terjadinya ketidakseimbangan perkembangan kawasan tersebut sehingga terjadinya alih fungsi lahan. Dalam hal ini Perencanaan Tata Ruang sebaiknya mengikuti apa yang sudah diatur oleh Pemerintah agar tidak merubah fungsi kawasan yang sudah dicantumkan pada Rencana Tata Ruang Kota. Peran aktif masyarakat yang melewati Jalan T.Umar diperlukan tidak semata-mata membatasi dan mengatur ruang gerak dan kegiatan masyarakat, akan tetapi juga memberi dorongan dan peluang agar masyarakat berpartisipasi pula dalam kegiatan penataan ruang dengan menaati peraturan yang ada.Kata kunci Bangkitan dan tarikan, RTRW, Tata Ruang Kota.